Pengaruh Pendidikan Kesehatan Audiovisual Berbabsis Self Management terhadap Pasien Hipertensi - Olviani, Yurida; Saherna, Jenny; Hadrianti, Dessy; Satriani, Desy; Aulia, Nazi Ratul (Jurnal Skala Kesehatan, 2026)
Hypertension remains the leading non-communicable disease, causing numerous complications and deaths. Complications of hypertension can be prevented through health promotion, specifically by providing hypertension self-management education using audiovisual media adapted to the current development of information technology. Developing accessible, widely reachable, efficient, and effective audiovisual health education media on hypertension self-management is essential to encourage the community to regularly monitor blood pressure and independently adopt routine behavior changes to prevent further complications. Objective: To develop audiovisual health education media on hypertension self-management for patients with hypertension. Methods: Quasi-experimental study. Data were analyzed using the Wilcoxon Paired Sample T-Test.